(untitled) (Research, Society and Development, 2021)
Allergy to Cow’s Milk Protein (ACMP) is a food allergy, more common in children, and it is triggered by an immune response. Lactose Intolerance (LI) is related to lactose malabsorption due to inactivity or deficiency of lactose enzyme. The objective of this study is to demonstrate these two conditions and their diagnosis and treatment. The diagnosis of ACMP is made through anamnesis, physical test, antibody research and the Oral Provocation Test. The primary treatment is the exclusion of cow’s milk consumption, which can include the use of corticosteroids and antihistamines. The diagnosis of LI can be performed by tolerance test and measurement of lactase activity. The treatment of LI is the suspension of milk consumption and/or the therapy of replacement of the enzyme lactase. The Food Detective method is not suitable for ACMP or LI diagnostics. Both conditions diagnosis should be made with caution, since the exclusion of milk from diet may interfere with the nutrient levels needed, especially in children.